Implementation of the Rapid Game Prototyping Method in the Educational Game E-Rush Using Unity 2D Engine - Aziezah, Nur; Muhammad Fawwaz Naufal; Andini Tribuana Tunggadewi; Rosyda Dianah; Rina Martini (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Technological development has progressed rapidly, including in the field of education. One result is educational games, which are practical and engaging tools for delivering content, such as environmental awareness training. Games today offer more than entertainment; they can foster interactive learning. This study developed an Android-based educational game, E-Rush, to increase youth awareness about waste sorting. The game employs a drag-and-drop interface, allowing players to classify waste into three categories: organic, inorganic, and hazardous (B3). It features gamification elements, such as scoring, time challenges, and enemy robots, to boost engagement. The development method used was Rapid Game Prototyping, which enabled quick iterations in design and testing. Requirement analysis identified user and system needs, followed by the design of storyboards, 2D models, and UML diagrams (Use Case and Activity). Blackbox Testing evaluated functionality from the user’s perspective. The results show that E-Rush was successfully implemented with functional features such as scoring, levels, NPC enemies, and time limits. All components met the defined requirements. In conclusion, E-Rush can be an effective alternative learning medium for promoting early waste segregation habits and supporting environmental education programs.